Genetic analysis of 23 Y-STR loci in the Va population from Yunnan Province, Southwest China - Jing Yuan; Lei Huang; Yuan Yin; Xiufeng Zhang (Taylor & Francis Group, 2023)
Background Y-chromosomal short tandem repeat (Y-STR) polymorphisms are widely used in forensic DNA analysis. However, there is a lack of information about the Chinese Va population in the Y-STR Haplotype Reference Database. Aim To establish the Y-chromosome Haplotype Reference Database of the Yunnan Va population and investigate the population genetic relationships with other geographically adjacent groups. Subjects and methods In total, 23 Y-STR loci were genotyped with the PowerPlex Y23 Kit in 368 unrelated healthy Va males from Yunnan Province, Southwest China. Genetic polymorphism was analysed using the YHRD's AMOVA tools and the MEGA 6.0 software. Results The gene diversity (GD) of the 23 Y-STR loci ranged from 0.3092 (DYS19) to 0.7868 (DYS385a/b). According to haplotype analysis, 204 different haplotypes were obtained, out of which 144 were unique. The haplotype diversity (HD) and discrimination capacity (DC) were 0.9852 and 0.5543, respectively. By comparing the Yunnan Va group with the other 22 referential groups, the results revealed that Yunnan Va was isolated from other groups. Conclusions The 23 Y-STR loci were highly polymorphic and informative in the Yunnan Va population, and the results enriched the basic genetic information for forensic investigation and population genetic studies.